Nano-híbridos magnéticos : Preparação, caracterização e testes de adsorção em efluentes sintéticos ricos em ácido bórico - Pinotti, Camila Nunes (2023)
In this work, a binary magnetic nanohybrid was developed from the precursors CoFe2O4 and MgO, produced by the Sol-Gel method, as well as ternary nanohybrids from co-precipitated γFe2O3 and MgO nanoparticles (NPs) decorated on zeolite 5A (Z5A) molds. For the CoFe2O4/MgO nanohybrid, X-ray diffraction, scanning electron microscopy, infrared spectroscopy, 57Fe Mössbauer spectroscopy, and magnetization measurements have indicated that the ferrimagnetic nanocrystalline phase of CoFe2O4 is surrounded by the paramagnetic phase of MgO, with the latter behaving as a matrix for the CoFe2O4 NPs. The CoFe2O4/MgO nanohybrid was applied to boron compounds removal from synthetic effluents, showing up to 92% removal capacity. After the boron adsorption process on the MgO surface, the results of X-ray diffraction, scanning electron microscopy, and infrared spectroscopy showed the formation of crystalline Mg(OH)2 (with needle-like structures), while 57Fe Mössbauer spectroscopy has indicated that the fraction of Fe3+ ions in the nanograin surfaces was changed compared to the original adsorbents. For the ternary nanohybrids, 57Fe Mössbauer and transmission electron microscopy data indicated a broad particle size distributionof γ-Fe2O3 NPs. These γ-Fe2O3 are strongly affected by size effects, with those smaller than 10 nm having an octahedral/tetrahedral iron site ratio of 7/3 instead of the 5/3 ratio found in the bulk. 27Al nuclear magnetic resonance (NMR) showed the formation of octahedral Al species after boric acid reaction with MgO NPs. 11B NMR spectrum indicated adsorption of B on the MgO/Z5A surface, whereas B adsorption on the pure Z5A framework was absent. Adsorption isotherms and kinetic studies of the binary nanohybrid demonstrated that the adsorption of boron-rich species is described by Freundlich and Pseudo-First-order models, respectively, while in ternary nanohybrids, Freundlich and fractal-like models were observed. Boron adsorption occurs predominantly by the MgO fraction in both cases, and both showed good boron removal efficiency when compared to other materials reported in the literature.